Selective Catalytic Frustrated Lewis Pair Hydrogenation of CO2 in the Presence of Silylhalides - Wang, Tongtong; Xu, Maotong; Jupp, Andrew R.; Qu, Zheng‐Wang; Grimme, Stefan; Stephan, Douglas W. (Angewandte Chemie International Edition, 2021)
The frustrated Lewis pair (FLP) derived from 2,6‐lutidine and B(C6F5)3 is shown to mediate the catalytic hydrogenation of CO2 using H2 as the reductant and a silylhalide as an oxophile. The nature of the products can be controlled with the judicious selection of the silylhalide and the solvent. In this fashion, this metal‐free catalysis affords avenues to the selective formation of the disilylacetal (R3SiOCH2OSiR3), methoxysilane (R3SiOCH3), methyliodide (CH3I) and methane (CH4) under mild conditions. DFT studies illuminate the complexities of the mechanism and account for the observed selectivity. The frustrated Lewis pair (FLP), 2,6‐lutidine/ B(C6F5)3 mediates the catalytic reduction of CO2 using H2 and a silylhalide. Control of the silylhalide and solvent, affords selective avenues to the disilylacetal (R3SiOCH2OSiR3), methoxysilane (R3SiOCH3), methyliodide (CH3I) and methane (CH4) under mild conditions. The mechanism is studied by DFT and accounts for the observed selectivity.